Exploring the Dynamic Relationship: How Exchange Rates Drive Company Valuation through Foreign Portfolio Investments - Endi Rustendi, Endi (Manageable, 2023)
This study aims to analyze the influence of economic growth and exchange rates on firm value with foreign portfolio investment as an intervening variable at PT Bank Central Asia Tbk. for the period 2011-2020. Quarterly secondary data from 2011-2020 were utilized. The data were then processed using EViews 11 Version analysis tool. The analysis employed descriptive statistics, linear tests, and classical assumption tests. Hypothesis testing was conducted using Partial Test (T-Test). The results of the partial test (T-Test) indicate that economic growth, exchange rates, and foreign portfolio investment insignificantly influence firm value. However, regarding the intervening variable, foreign portfolio investment does not mediate the influence of economic growth (GDP) on firm value, either directly or indirectly, and foreign portfolio investment also does not directly mediate the influence of exchange rates on firm value. Nonetheless, exchange rates directly affect foreign portfolio investment, thus reinforcing the relationship between exchange rates and firm value. Therefore, the fifth hypothesis is accepted.